2023
DOI: 10.1186/s13018-023-04419-8
|View full text |Cite
|
Sign up to set email alerts
|

The potentially dangerous zone of the dorsomedial cutaneous nerve in minimally invasive surgery for hallux valgus: a cadaveric study

Zhaolin Teng,
Xiang Geng,
Jiafeng Song
et al.

Abstract: Background This study aims to describe the distribution of the dorsomedial cutaneous nerve (DMCN) in the middle and proximal parts of the metatarsal from a lateral view. The purpose is to provide guidance to surgeons in protecting the nerve during the 3rd and 4th generation minimally invasive surgery (MIS) for hallux valgus (HV). Methods A total of 20 cadaveric feet were dissected to expose the course of the DMCN and sentinel vein. Measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(29 reference statements)
0
1
0
Order By: Relevance
“… 11 It has been reported that the dorsomedial cutaneous nerve is most vulnerable in MIS for HV, surgeons need to have deep anatomical knowledge and meticulous surgical techniques to avoid neurovascular injury. 12 , 13 Moreover, how to correct multi‐directional deformities in HV in MICA remains difficult because of previous osteotomy design, limited operating space and instruments. The so‐called fourth generation of MIS has been raised to cover the shortage of MICA.…”
Section: Introductionmentioning
confidence: 99%
“… 11 It has been reported that the dorsomedial cutaneous nerve is most vulnerable in MIS for HV, surgeons need to have deep anatomical knowledge and meticulous surgical techniques to avoid neurovascular injury. 12 , 13 Moreover, how to correct multi‐directional deformities in HV in MICA remains difficult because of previous osteotomy design, limited operating space and instruments. The so‐called fourth generation of MIS has been raised to cover the shortage of MICA.…”
Section: Introductionmentioning
confidence: 99%